Charcot-Marie-Tooth disease in Denmark: a nationwide register-based study of mortality, prevalence and incidence. Issue 11 (3rd November 2017) - Vaeth, Signe; Vaeth, Michael; Andersen, Henning; Christensen, Rikke; Jensen, Uffe Birk
Abstract : Objectives: Charcot-Marie-Tooth disease (CMT) is the most common inherited disorder of the peripheral nervous system, yet no studies have compared the mortality in patients with CMT with that of the general population, and prevalence estimates vary considerably. We performed a nationwide register-based study to investigate the prevalence, incidence and mortality of CMT in Denmark. Design: We used the Danish National Patient Registry to select all records with primary diagnostic codes for CMT between 1977 and 2012 given at a neurological, neurophysiological, paediatric or clinical genetic clinic. The prevalence was estimated by 31 December 2012, and the incidence rate was calculated based on data from 1988 to 2012. We calculated a standardised mortality ratio (SMR) and an absolute excess mortality rate (AER) stratified according to age categories and disease duration. Results: A total of 1534 patients (652 women) were identified. The prevalence proportion was 22.5 per 100 000 (95% CI 21.2 to 23.7) and the incidence rate was 0.98 (95% CI 0.93 to 1.04) per 100 000 person-years. The SMR was 1.36 (95% CI 1.21 to 1.53), and the AER was 4.87 per 1000 person-years (95% CI 2.77 to 6.96). We found a significantly higher SMR in cases below 50 years of age, and in cases with disease duration of more than 10 years. Conclusions: We found a reduced life expectancy among patients diagnosed with CMT. To our knowledge, this is the first study of CMT to use nationwide register-based data, and the first to report an SMR and an AER.